Insights from modeling and observational evaluation of a precipitating continental cumulus event observed during the MC3E field campaign. Issue 5 (13th March 2015) - Mechem, David B.; Giangrande, Scott E.; Wittman, Carly S.; Borque, Paloma; Toto, Tami; Kollias, Pavlos
Abstract: A case of shallow cumulus and precipitating cumulus congestus sampled at the Atmospheric Radiation Measurement Program Southern Great Plains supersite during the Midlatitude Continental Convective Clouds Experiment is analyzed using a multisensor observational approach and numerical simulation. Observations from a new radar suite surrounding the facility are used to characterize the evolving statistical behavior of the precipitating cloud system. This is accomplished using distributions of different measures of cloud geometry and precipitation properties. Large‐eddy simulation (LES) with size‐resolved (bin) microphysics is employed to determine the forcings most important in producing the salient aspects of the cloud system captured in the radar observations. Our emphasis is on assessing the importance of time‐varying versus steady state large‐scale forcing on the model's ability to reproduce the evolutionary behavior of the cloud system. Additional consideration is given to how the characteristic spatial scale and homogeneity of the forcing imposed on the simulation influences the evolution of cloud system properties. Results indicate that several new scanning radar estimates such as distributions of cloud top are useful to differentiate the value of time‐varying (or at least temporally well‐matched) forcing on LES solution fidelity. Key Points: New ARM scanning radars can highlight differences in numerical simulations Simulations constrained to observations captured key aspects of the cloud event More complete observations are required to constrain 3‐D cloud behavior